Sustainable Consumer Behavior and Food Marketing - Meixner, Oliver; Riefler, Petra; Schanes, Karin; Meixner, Oliver; Riefler, Petra; Schanes, Karin (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In light of the considerable impact of global food supply chains on climate change, more sustainable ways of producing, distributing, and consuming food appear critical for sustainable development. With the aim of contributing to this topic, this Special Issue on sustainable food consumption and food marketing addresses various relevant issues related to food consumption, including innovative and sustainable forms of food production and consumption, animal welfare and meat consumption, price transmission, social media communication, alternative food production, and organic agriculture, among others. As such, this Special Issue sheds light on more sustainable and carbon-friendly food production and consumption systems from various angles. It delivers valuable scientific evidence for the transformation of current carbon-based food supply chains to more eco-friendly, fair, and future-oriented food supply chains.
English
Keywords: Research & information: general; aquaponics; Structural Equation Modeling; consumer behavior; purchase intention; willingness to pay; sustainability; food market; veganic; vegan-organic; vegan; stockless; attitudes; environmental marketing; green product; green consumer; green purchase decision; consumer behaviour; theory of planned behaviour; sustainable consumption; Bangladesh; out-of-home catering; sustainable nutrition; variety seeking; spontaneous choice; company canteens; trust; social media; small and medium enterprises; Bresse Gauloise; choice experiment; dual-purpose breeds; faba beans; Kollbecksmoor; theory of planned behavior; Vorwerkhuhn; White Rock; green products; palm oil free; structural equation modeling; SEM; sustainable food consumption; food waste; theoretical framework; food tourism; community-based tourism; sustainable development; community engagement; rural development; food heritage; carbon-friendly food; emotions; animal welfare; cured ham; discrete choice experiment; latent construct model; market instability; nonlinear empirical dynamics; n/a